Analysis of Factors that Influence Investor Interest in Investing in Islamic Mutual Funds (Case Study: Java Island Region) - Dzikri, Mohd. Iqbal; Hasanah, Neneng; Hasanah, Qoriatul (Tazkia Islamic Finance and Business Review, 2023)
Sharia mutual fund investment in Indonesia continued to experience positive developments as an investment instrument. However, the fact was that the nav of Islamic mutual funds was still unable to closed the gaped with the total nav of conventional capital markets as a whole. The purpose of this studied was to analyze the factors that influence investors' decisions in investing in Islamic mutual funds. The method used in this researched was sem-pls. Respondent criteria in this studied was sharia mutual fund investors and domiciled in a province on the island of java. The theoretical approached in this studied was the theory of planned behavior with variabels of motivation, knowledge, re-perception, technological advances, and product information. The results of this studied indicate that the variabels motivation, knowledge, perceived returned, advances in technology, and product information had a positive and significant influence on investment intentions. The results of this studied could been used by securities companies and regulators to increase the number of investors or planning policies regarding Islamic mutual funds. Keywords: Investment, Capital Market, Investor Interest, Sharia Mutual Funds.